(untitled) (REMUNOM, 2025)
This study aimed to analyze the negotiation focuses used in the purchasing processes of small businesses operating in a peripheral area of ​​Manaus. The survey method was used, with data collected through semi-structured interviews, all nominal, analyzed using semantic techniques and content analysis, organized in the form of synthesizing tables, and with results interpreted comparatively against the elaborated theoretical framework. The results showed a) eight negotiation focuses practiced, with price being the most common focus, b) they are used when buyers do not have money or feel some need, c) they are applied by strictly distributive and competitive means, and d) the benefits are mainly the exclusive satisfaction of the buyers’ interests, to the detriment of the objectives of sellers and clients. The conclusion shows that the focus of the negotiations that small merchants in the periphery of Manaus engage in during their purchases is exclusively distributive, competitive, and selfish.